The artist's way: A spiritual path to higher creativity - Cameron, Julia (New York Jeremy P. Tarcher, 1992)
"A comprehensive twelve-week program to recover your creativity from a variety of blocks, including limiting beliefs, fear, self-sabotage, jealousy, guilt, addictions, and other inhibiting forces, replacing them with artistic confidence and productivity."